2021
DOI: 10.1088/1755-1315/637/1/012044
|View full text |Cite
|
Sign up to set email alerts
|

The phytoextraction of Cu and Zn by elephant grass (Pennisetum purpureum) from tropical soil 21 years after amendment with industrial waste containing heavy metals

Abstract: Increased soil heavy metal concentrations are suggested to cause roots to work harder. This research was to study the growth and phytoextraction behaviors of elephant grass in soil amended with industrial waste. Soil samples were obtained from an experimental field treated with a heavy metal containing waste at 0, 15 and 60 Mg ha-1, CaCO3 at 0 and 5 Mg ha-1, and compost at 0 and 5 Mg ha-1. Soil samples were planted with elephant grass, 8 weeks after which the soil samples were analyzed for Cu and Zn. Plant roo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 19 publications
5
6
0
Order By: Relevance
“…Analysis of variance (Anova) indicates that waste level significantly depressed the plant height and plant biomasses (roots, shoots, and the whole plant) and significantly enhanced the soil concentrations of Cu and Zn (Table 2). Our previous researches also showed that the waste borne Cu and Zn in the soils depressed the growth of several plants including corn plant, water spinach, caisim, lettuce, and napier grass [20][21][22]. The phenomena were also in accordance with various researches previously reported [14][15][16][17].…”
Section: The Growth and Heavy Metal Uptake Of Corn Plant In Waste-ame...supporting
confidence: 89%
See 1 more Smart Citation
“…Analysis of variance (Anova) indicates that waste level significantly depressed the plant height and plant biomasses (roots, shoots, and the whole plant) and significantly enhanced the soil concentrations of Cu and Zn (Table 2). Our previous researches also showed that the waste borne Cu and Zn in the soils depressed the growth of several plants including corn plant, water spinach, caisim, lettuce, and napier grass [20][21][22]. The phenomena were also in accordance with various researches previously reported [14][15][16][17].…”
Section: The Growth and Heavy Metal Uptake Of Corn Plant In Waste-ame...supporting
confidence: 89%
“…For examples, [21] reported that the dry weight of caisim decreased by 38.1%, while those of water spinach and lettuce decreased by 52% and 100%, respectively, in soil amended with Cu-containing waste at 60 Mg ha -1 . Several other soil workers also reported the negative effects of heavy metals on the growth and production of agricultural commodities and grasses like napier grass (Penissetum purpureum) [12,17,[22][23][24] . The above problem must be solved.…”
Section: Introductionmentioning
confidence: 99%
“…The root/shoot was shown to positively and linearly correlate with the soil-heavy metal concentration. The writer in [64] stated that higher root weight may cause higher root cation exchange capacity (CEC) that may retain The growth of several plants in heavy metal contaminated soil (S1 control, S2 low heavy metals, S3 high heavy metals; lettuce dead in S3, WAP weeks after planting) (after [63] with permission). more heavy metal cations on the surface of plants' roots so that less heavy metals may move to plant shoots.…”
Section: Effects Of High Concentrations Of Heavy Metals On Plant Growthmentioning
confidence: 99%
“…Higher CEC can be attained by increasing soil pH [2,65]. Plant roots also produce some exudates such as low molecular organic acids The relationship between the root/shoot and the soil DTPA extracted Cu and Zn (after [64] with permission).…”
Section: Effects Of High Concentrations Of Heavy Metals On Plant Growthmentioning
confidence: 99%
See 1 more Smart Citation